Gaya GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP IT AL-IRSYAD AL-ISLAMIYYAH KARAWANG - Ludin Lestari, Rival; Akil; Agus Susilo Saefullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the principal's leadership style and analyze its tangible contribution to improving teacher performance at SMP IT Al-Irsyad Al-Islamiyyah Karawang. This study used a descriptive qualitative approach with purposive sampling. Data collection was conducted through direct observation, semi-structured interviews, and documentation. The results indicate that the principal implements a synergy of three primary leadership styles: collaborative/participatory, transformational, and Islamic (uswah hasanah). This approach has been proven to have a positive and significant impact on four aspects of teacher performance: systematic planning, innovative learning implementation integrated with Islamic values, objective evaluation, and high levels of discipline and commitment. This performance improvement is realized through motivational strategies, educational supervision (hisbah), an appreciation system (rewards), and direct role modeling (lead by example). It is concluded that this leadership model is highly effective in creating a productive, harmonious, supportive, and religious school ecosystem, thus motivating teachers professionally and inspiring them spiritually in carrying out their educational mandate.